The Effect Of Corporate Culture On Sustainability Report Quality - Atika, Atika; Simamora, Alex Johanes (Jurnal Akuntansi, 2024)
This research aims to examine the effect of corporate culture on sustainability report quality. The total research samples are 68 observations on the index of Sri Kehati. Corporate culture includes cultures of clan, adhocracy, hierarchy, and market. Sustainability report quality is measured by the scoring method. Data analysis uses regression tests. Based on data analysis, low clan culture, high hierarchy culture, and high market culture lead to high sustainability report quality. However, there is no effect of adhocracy culture on sustainability report quality. This research contributes to investigating how far the implementation of POJK no. 51/POJK.03/2017 can lead firms to have high-quality sustainability reports. This research also contributes to providing evidence in emerging countries such as Indonesia.